Blind supratemporal retrobulbar block in cats: a feasibility cadaveric study and its efficacy in a group of subjects undergoing corneal or intraocular surgery - Elena Lardone; Manuela Crasta; Pier Carlo Ostan; Paola Gherlinzoni; Alessandra Landi; Paolo Franci (Frontiers in Veterinary Science)
IntroductionThe supratemporal retrobulbar block (RB) has not been comprehensively described in cats.Materials and methodsCadaveric study: a modified supratemporal retrobulbar injection of 0.1 ml/kg of iomeprole and saline (1:3) was executed using a Tuohy needle in recently deceased cats. Cadavers underwent computed tomography before and following injections. Injectate distribution within the intraconal space was evaluated. Extraconal injections were considered a failure. Clinical study: cats undergoing corneal/intraocular surgery were included. After intramuscular premedication with methadone 0.3 mg/kg, dexmedetomidine 3 mcg/kg and alfaxalone 2 mg/kg and induction with intravenous (IV) alfaxalone to effect, isoflurane anesthesia was maintained with a target end-expired fraction of 1.1%. Cats were randomly allocated in the retrobulbar group [RG, receiving a modified supratemporal RB with 0.1 ml/kg of a mixture of 2% lidocaine (5.5 ml) and 0.75% ropivacaine (2 ml)] or control group (CG). When heart rate or mean arterial pressure increased above 20% of the pre-incisional values, fentanyl (1 mcg/kg IV) was administered. Alfaxalone (0.5 mg/kg IV) was injected when anesthesia was deemed too light. After a total of 3 interventions regardless the type of drugs (fentanyl/alfaxalone), a constant rate infusion of fentanyl (5 mcg/kg/h IV) was started. Anesthetist interventions, quality of recovery (blindly assessed using a descriptive score scale), postoperative eye rubbing, complications were studied.ResultsIn the cadaveric study 8 eyes were included (success rate = 87%). The contrast agent spread was scored “moderate-to-large” or “large” in 85.7% of cases and a median 360° (180–360) distribution around the optic nerve was reported. In the clinical study 12 cats were included (6 in RG, 6 in CG). The median time to perform the RB was 35 s (20–50). Only the controls required anesthetist interventions [total amount of 6 (p = 0.0276): fentanyl (3/6) and alfaxalone (2/6)]. The RG had a significantly better recovery score (p = 0.0012) than CG. Only controls showed eye rubbing (3/6).ConclusionsThe modified supratemporal RB is an achievable and rapidly performed technique. In this study it reduced intraoperative drug administration and improved recovery quality in cats undergoing corneal or intraocular surgery.